Comparing the effect of a consult model versus an integrated palliative care and medical oncology co-rounding model on health care utilization in an acute hospital – an open-label stepped-wedge cluster-randomized trial. (September 2021) - Yang, Grace M; Zhou, Siqin; Xu, Zhizhen; Goh, Stella SL; Zhu, Xia; Chong, Dawn QQ; Tan, Daniel SW; Kanesvaran, Ravindran; Yee, Alethea CP; Neo, Patricia SH; Cheung, Yin-Bun
Background: The benefit of specialist palliative care for cancer inpatients is established, but the best method to deliver specialist palliative care is unknown. Aim: To compare a consult model versus a co-rounding model; both provide the same content of specialist palliative care to individual patients but differ in the level of integration between palliative care and oncology clinicians. Design: An open-label, cluster-randomized trial with stepped-wedge design. The primary outcome was hospital length of stay; secondary outcomes were 30-day readmissions and access to specialist palliative care. ClinicalTrials.gov number NCT03330509. Setting/participants: Cancer patients admitted to the oncology inpatient service of an acute hospital in Singapore. Results: A total of 5681 admissions from December 2017 to July 2019 were included, of which 5295 involved stage 3-4 cancer and 1221 received specialist palliative care review. Admissions in the co-rounding model had a shorter hospital length of stay than those in the consult model by 0.70 days (95%CI −0.04 to 1.45, p = 0.065) for all admissions. In the sub-group of stage 3-4 cancer patients, the length of stay was 0.85 days shorter (95%CI 0.05–1.65, p = 0.038). In the sub-group of admissions that received specialist palliative care review, the length of stay was 2.62 days shorter (95%CI 0.63–4.61, p = 0.010). Hospital readmission within 30 days (OR1.03, 95%CI 0.79–1.35, p = 0.822) and access to specialist palliative care (OR1.19, 95%CI 0.90–1.58, p = 0.215) were similar between the consult and co-rounding models. Conclusions: The co-rounding model was associated with a shorter hospital length of stay. Readmissions within 30 days and access to specialist palliative care were similar.